What Happens After the Demonstration Phase? The Sustainability of Canada's At Home/Chez Soi Housing First Programs for Homeless Persons with Mental Illness. Issue 1 (30th January 2017) - Nelson, Geoffrey; Caplan, Rachel; MacLeod, Timothy; Macnaughton, Eric; Cherner, Rebecca; Aubry, Tim; Méthot, Christian; Latimer, Eric; Piat, Myra; Plenert, Erin; McCullough, Scott; Zell, Sarah; et al.
Abstract: This research examined the sustainability of Canada's At Home/Chez Soi Housing First (HF) programs for homeless persons with mental illness 2 years after the end of the demonstration phase of a large (more than 2000 participants enrolled), five‐site, randomized controlled trial. Qualitative interviews were conducted with 142 participants (key informants, HF staff, and persons with lived experience) to understand sustainability outcomes and factors that influenced those outcomes. Also, a self‐report HF fidelity measure was completed for nine HF programs that continued after the demonstration project. A cross‐site analysis was performed, using the five sites as case studies. The findings revealed that nine of the 12 HF programs (75%) were sustained, and that seven of the nine programs reported a high level of fidelity (achieving an overall score of 3.5 or higher on a 4‐point scale). The sites varied in terms of the level of systems integration and expansion of HF that were achieved. Factors that promoted or impeded sustainability were observed at multiple ecological levels: broad contextual (i.e., dissemination of research evidence, the policy context), community (i.e., partnerships, the presence of HF champions), organizational (i.e., leadership, ongoing training, and technical assistance), and individual (i.e., staff turnover, changes, and capacity). The findings are discussed in terms of the implementation science literature and their implications for how evidence‐based programs like HF can be sustained.